Steam and Gas Turbines and Power Plant Engineering - Yadav (R); Sanjay; Rajay ("18-C, Sarojoni Naidu MargAllahabad", 2006)
Steam ; Gas Turbines ; Power Plant Engineering
Keywords: Steam ; Gas Turbines ; Power Plant Engineering